(untitled) (Bangladesh Journal of Animal Science, 2014)
Fibrous feeds mostly of crop residues, green grasses, and tree foliages and leaves support bulk diets of farm animals being raised mostly by smallholders. The roughage DM produced (51056 million kg) surpasses its demand (49200 million Kg) by 3.77%, but losses and otherwise uses result in production deficit of 44.5%. An average 56.2% deficit of roughage DM and 80.0% of concentrate DM results in a very poor plane of nutrition for farm animals. It supports an average diet containing 6.75 MJME/Kg DM and 1.63% DCP with the feed produced or 7.74 MJME/Kg DM and 2.32% DCP with the feed available, while a miserly calculation demands an average diet of at least 6.50 MJME/ Kg DM and 4.50% DCP. Brans and oilcakes sharing the bulk amount of concentrate feeds, except cereal maize being produced recently, often limit options for formulation of diets of higher metabolizability and quality protein including balancing of micronutrients essential for supporting nutritional planes for high yielding animals. Annual biomass demand and supply mismatch, harvest loss, bulk transfer problem, and otherwise uses of fibrous residues further limit feed supply to animals irrespective of their quality. Commercial poultry, on the other hand, is largely based on imported feeds except a part of corn. Different form of premixes, steroids, antibiotics and enzymes with or without knowing their quality and residual impacts on human health also used for poultry and bovine animals posing threats to food safety sometimes. The present poor plane of nutrition is not conducive to support an increased production of local or crossbred animals. Diversification and production of quality feeds and fodders, synchronization of feed production and availability to animals, strengthening feed milling capacity, conservation and improvement of new pasturage systems, mitigation of climate change impacts and domestic protection to feed safety and quality feed import are some of the options forward to increased supply of feeds and fodders help increased production and productivity of farm animals in the country. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19378 Bang. J. Anim. Sci. 2014. 43 (1): 1-10